Testosterone Therapy, Thrombophilia–Hypofibrinolysis, and Hospitalization for Deep Venous Thrombosis-Pulmonary Embolus: An Exploratory, Hypothesis-Generating Study. (April 2014) - Glueck, Charles J.; Richardson-Royer, Caitlin; Schultz, Reiker; Burger, Tim; Bowe, Dedrick; Padda, Jagjit; Wang, Ping
In our study of 596 men hospitalized in the last 3 years for deep venous thrombosis-pulmonary emboli (DVT-PE), we determined the prevalence of exogenous testosterone (T) use with subsequent development of DVT-PE. Of the 596 men, 110 were now dead, 97 had cancer thought to cause DVT-PE, 250 could not be contacted, leaving 139, of whom 7 had taken T before and at the time of their admissions, 1.2% of the total cohort, a conservative estimate of the prevalence of T-associated DVT-PE. In all, 5 of the 7 DVT-PE events occurred within 3 months of initiation of T, with mean and median intervals between initiation of T and hospitalization with DVT-PE 6.7 and 2 months. Of the 7 men treated with exogenous T, all 5 men who had evaluation of thrombophilia–hypofibrinolysis were found to have previously undiagnosed familial or acquired thrombophilia or hypofibrinolysis, suggesting a thrombotic interaction between exogenous T and thrombophilia–hypofibrinolysis.